The Unification of Gravitational Field and Electromagnetic Field - Yao, Kexin (European Journal of Applied Sciences, 2021)
It is pointed out that the magnetic field is not an independent real substance and it is considered that the electromagnetic field containing non-material magnetic field cannot establish a unified field theory with the gravitational field of the real substance. Through analysis, it is concluded that the so-called magnetic field is essentially a motion state of the electric field. The magnetic field is defined as the electric field contracting in motion. According to this definition, the Biot-Savart, Lorentz force, electromagnetic induction, displacement current and Ampere loop laws are deduced and proved. Through the experimental results of electrostatic field around the permanent magnet, it is proved that the magnetic field is indeed the electric field contracting in motion. It is believed that the electrostatic field is similar to the static gravitational field, the electric field contracting in motion can be defined as a magnetic field, and the gravitational field contracting in motion can also be defined as a similar contraction field, so that the electromagnetic field is completely similar to the gravitational contraction field, and the unification of the two fields is an inevitable result.